The Influence of Islamicity Performance Index and Intellectual Capital on Sharia Business Unit Profitability - Cahaya Fitriana Dewi Amala; Ely Windarti Hastuti; Meidina Nur Nabilah; Malihatin Malihatin; Citra Amanda (FEBI UIN Sunan Kalijaga, 2022)
Sharia Business Unit in Indonesia is experiencing increasingly rapid growth. Islamic financial institutions establish profitability as a measuring tool to improve financial performance. Several ratios can be used to take measurements on profitability, such as Islamicity Performance Index and Intellectual Capital. The study aims to analyze the influence of Islamicity Performance Index and Intellectual Capital on profitability in Sharia Business Units in Indonesia. This type of research is quantitative. The sample used is 16 Sharia Business Units in Indonesia for the period 2018-2020. The data analysis technique used is panel data regression, using the eviews 12 application program. The results showed that is partially Equitable Distribution Ratio, Islamic Income vs. Non-Islamic Income and Intellectual Capital had a significant positive influence on profitability. Simultaneously stated that the Islamicity Performance Index and Intellectual Capital have a significant effect on Profitability in sharia business units in Indonesia